Development of Eco-Aesthetic Competence of 1st Graders Through Mother Tongue and Reading Literacy Textbooks - Alijonova Maftunaxon Maxamadjon Qizi (Zien Journals, 2023)
This article explores the meaning and content of the formation of eco-aesthetic competence in the minds of students on the basis of information and assignments that are practically given in existing textbooks, the scientific analysis of the epistemological and ontological approach, which is most effective for understanding the essence of environmental competence. How important project-based education is for today, for the formation and development of eco-aesthetic competence, will be analyzed in the article.
Keywords: project-based education; competence; favors of nature